Myosin‐IIA regulates leukemia engraftment and brain infiltration in a mouse model of acute lymphoblastic leukemia. Issue 1 (20th January 2016) - Wigton, Eric J.; Thompson, Scott B.; Long, Robert A.; Jacobelli, Jordan
Abstract : MyoIIA regulates leukemia cell engraftment and dissemination into the brain, by promoting TEM of Bcr‐Abl + ALL cells. Abstract : Leukemia dissemination (the spread of leukemia cells from the bone marrow) and relapse are associated with poor prognosis. Often, relapse occurs in peripheral organs, such as the CNS, which acts as a sanctuary site for leukemia cells to escape anti‐cancer treatments. Similar to normal leukocyte migration, leukemia dissemination entails migration of cells from the blood circulation into tissues by extravasation. To extravasate, leukemia cells cross through vascular endothelial walls via a process called transendothelial migration, which requires cytoskeletal remodeling. However, the specific molecular players in leukemia extravasation are not fully known. We examined the role of myosin‐IIA a cytoskeletal class II myosin motor protein, in leukemia progression and dissemination into the CNS by use of a mouse model of Bcr‐Abl‐driven B cell acute lymphoblastic leukemia. Small hairpin RNA‐mediated depletion of myosin‐IIA did not affect apoptosis or the growth rate of B cell acute lymphoblastic leukemia cells. However, in an in vivo leukemia transfer model, myosin‐IIA depletion slowed leukemia progression and prolonged survival, in part, by reducing the ability of B cell acute lymphoblastic leukemia cells to engraft efficiently. Finally, myosin‐IIA inhibition, either by small hairpin RNA depletion or chemical inhibition by blebbistatin, drastically reduced CNS infiltration of leukemia cells. The effects on leukemia cell entry into tissues were mostly a result of the requirement for myosin‐IIA to enable leukemia cells to complete the transendothelial migration process during extravasation. Overall, our data implicate myosin‐IIA as a key mediator of leukemia cell migration, making it a promising target to inhibit leukemia dissemination in vivo and potentially reduce leukemia relapses.